2020
DOI: 10.4155/fmc-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel and Selective CDK4/6 Inhibitors By Pharmacophore and structure-based Virtual Screening

Abstract: Aim: CDK4 and 6 are the key initiators in the transition from G1 to S phase in the cell cycle; thus, inhibition of CDK4/6 is a promising strategy for cancer treatment. Materials & methods: The Specs database and an in-house library were screened via the pharmacophore model and LibDock protocol and then the retrieved hits were clustered into 100 clusters. The CDK4/6 inhibitory activity of selected compounds was evaluated by CDK enzymatic assays, followed by chemical optimization of the top hit compound. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…To obtain a novel dual CDK6/PIM1 inhibitor, a combination of the pharmacophorebased and structure-based virtual screening program was conducted. 20 10 pharmacophore models were generated through a training set that contained four approved CDK6 inhibitors (Figure S1) and then validated through a decoy set which consisted of active (A-1−A-6, Figure S2) and inactive molecules (U-1−U-9, Figure S2). The result of pharmacophore validation is shown in the form of a heat map (Figure S3A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…To obtain a novel dual CDK6/PIM1 inhibitor, a combination of the pharmacophorebased and structure-based virtual screening program was conducted. 20 10 pharmacophore models were generated through a training set that contained four approved CDK6 inhibitors (Figure S1) and then validated through a decoy set which consisted of active (A-1−A-6, Figure S2) and inactive molecules (U-1−U-9, Figure S2). The result of pharmacophore validation is shown in the form of a heat map (Figure S3A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…2,724 ligands were reserved and further clustered into 100 clusters, then 15 compounds were selected for DYRK2 inhibitory activity evaluation (Supplementary Fig. 3 ) 39 . Among these 15 compounds, compound 12 was identified as a top hit, which displayed potent inhibition on DYRK2 with a half maximal inhibitory concentration (IC 50 ) value of 263 nM (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the online method FTMap () was used to predict the binding site of DEPTOR (red, binding pocket of the DEP domain; blue, binding pocket of the PDZ domain, Figure B). Moreover, the Libdock protocol in DS2019 , was used to analyze the interaction between C3 and DEPTOR. As shown in Figure C,D, the binding mode suggested that the fluorine-substituted phenyl and the hydroxyl of C3 formed strong hydrogen bond (HB) interactions with DEPTOR via Lys-58 and Gln-200, respectively.…”
Section: Resultsmentioning
confidence: 99%